A Divine Love of Annemarie Schimmel: A Sufism Study of an Orientalist - Umar Faruq Thohir; Irma Rumtianing U.H. (Dialogia, 2021)
A divine love as the main basis of Sufism has become increasingly popular since Rabi'ah al-Adawiyah with the concept of al-hub teaches to fully dedicate love only to Allah. In line with that, the Sufism thought of Jalaluddin Rumi was born which expressed her love for Allah through poetic prose. Her unique expression of divine love makes Sufism scholars interested. Among them Annemarie Schimmel. She has made many researches from her interest in the concept of love in Sufism, even though She is not a follower of Islam. Herefore, her research is important to do to examine the Sufism thoughts of Annemarie Schimmel who also conveys her work with beautiful poems. The discussion in her literature research is carried out in a descriptive analytical manner towards Annemarie Schimmel's Sufism thought through various theories in Sufism. Her qualitative research concludes that Annemarie Schimmel's interest in writing poetry and writing in beautiful language is one thing in common with al-Rumi, although not all of Annemarie Schimmel's writings are written in poetry or prose. Annemarie Schimmel only saw Sufism from the outside, herefore she considered it unnecessary to convert to Islam. Annemarie Schimmel considers Sufism as a mystical teaching that also exists in other religions, such as Buddhism and Shinto. For her, the most important thing is to be able to carry out the teachings conveyed by Sufism, namely awareness of the Supra Logic, Wisdom, guidance, and Love, without having to change theological beliefs to become Moslem.